PHYTOCHEMICAL SCREENING AND IN VITRO ANTIOXIDANT ACTIVITIES OF LEAF EXTRACTS OF ALTERNANTHERA BRASILIANA (L). KUNTZE AND ALTERNANTHERA BETTZICKIANA REGEL. - O R, Kasthuri; B, Ramesh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The present study was carried out to determine the phytochemical constituents and in vitro antioxidant activities of leaf extracts of Alternanthera brasiliana (L). Kuntze (A. brasiliana) and Alternanthera bettzickiana regel (A. bettzickiana). Methods: Preliminary phytochemical screening was performed in petroleum ether, chloroform, acetone, ethanol, hydroethanolic and water extracts of leaves of A. brasiliana and A. bettzickiana. The level of alkaloids, flavonoids, total phenolic content, tannins, Vitamin C, Vitamin E, GSH, and total proteins were determined in hydroethanolic, ethanol, and water extracts. Antioxidant activity of the hydroethanolic leaf extracts of A. brasiliana and A. bettzickiana were determined by 2,2-diphenyl-1-picryl-hydrazyl-hydrate free radical scavenging assay, nitric oxide scavenging assay, superoxide anion scavenging assay, ferric reducing antioxidant power assay, total antioxidant capacity, and reducing power assay. Results: The phytochemical screening of six different extracts of A. brasiliana and A. bettzickiana revealed the presence of various phytonutrients. Quantitative analysis of secondary metabolites in ethanol, hydroethanolic and water extracts of leaves of A. brasiliana and A. bettzickiana showed the presence of high amount of secondary metabolites in the hydroethanolic extract. In vitro, antioxidant assay of two plant extracts revealed that A. bettzickiana was more potent than A. brasiliana in scavenging free radicals. Conclusion: The different extracts from A. brasiliana and A. bettzickiana and specifically the hydroethanolic extract of A. bettzickiana revealed several properties such as rich source of phytonutrients, higher free radical scavenging properties, and significant antioxidant capabilities. Therefore, the bioactive compound should be isolated in future studies and could be used as a safe and serve as a potential source of natural antioxidants.